The phytochemical study on the leaves extract of laurus nobilis / Maisarah Abdullah - Abdullah, Maisarah (2014)
This research was conducted to determine the phytochemical compounds in the leaves extract of Laurus nobilis. From the literature review, this plant is traditionally used to treat hysteria and emmenagogue. The infusion form of powdered fruits has shown diuretic and carminative properties. Fatty oil from the fruit is used externally to heal and relieve boils, sprains, bruises and rheumatism. Scientists all over the world performed the research on which compound that gives those effects. However, the major chemical composition of bay leaf extract has not yet fully discovered. Therefore, in this research the phytochemical compounds of leaves extract of L. nobilis were reviewed. The major compounds were isolated and identified from the leaves extract of L. nobilis. Four procedures were utilized in this study including extraction, identification and detection of compounds with Thin Layer Chromatography (TLC), purification with preparative TLC and analyzing organic compound with proton Nuclear Magnetic Resonance 1H-NMR. Three compounds were then successfully being isolated and further analyzed with 1H NMR. However, only one compound (Compound 2) gave significant chemical shift that can be analyzed. Meanwhile, the spectra for another two compounds only showed the solvent peak. It was suggested that compound 2 is a monoterpene which is a derivative of a terpenoid group. This suggestion was performed after referring with 9-hydroxy-a terpineol, a compound which was also a monoterpene. The comparison showed that there are some similarities with regards to the NMR peaks for both compounds. The only difference was the peak between 6.218 ppm to 6.250 ppm which was present only for compound 2. There might be another side chains or isolated hydrogens in compound 2 which partially resemble 9-hydroxy-a-terpineol. It is recommended that a larger scale of sample extraction can be conducted to obtain higher percentage of compound. It is also recommended that other method can be used to conduct this study such as Gas Chromatography.